An amino acid-based supramolecular nanozyme by coordination self-assembly for cascade catalysis and enhanced chemodynamic therapy towards biomedical applications. Issue 22 (4th October 2021) - Song, Enhui; Li, Yongxin; Chen, Lili; Lan, Xiaopeng; Hou, Changshun; Liu, Chunlei; Liu, Chunzhao
Abstract : We developed a supramolecular nanozyme through the strategy of multicomponent coordination self-assembly using a bio-derived amino acid, glucose oxidase and Fe 2+ as building blocks, which exhibited great potential towards biomedical applications. Abstract : The clinical translation of chemodynamic therapy has been highly obstructed by the insufficient intracellular H2 O2 level in diseased tissues. Herein, we developed a supramolecular nanozyme through a facile one-step cooperative coordination self-assembly of an amphipathic amino acid and glucose oxidase (GOx) in the presence of Fe 2+ . The results demonstrated that the supramolecular nanozyme possessed cascade enzymatic activity ( i.e., GOx and peroxidase), which could amplify the killing efficacy of hydroxyl radicals (˙OH) via self-supplying H2 O2, finally achieving synergistic starvation–chemodynamic cancer therapy in vitro . Additionally, this cascade nanozyme also exhibited highly effective antibacterial activity on Escherichia coli ( E. coli ) and Staphylococcus aureus ( S. aureus ) without the need for additional H2 O2 . This work provided a promising strategy for the design and development of nanozymes for future biomedical applications.